Metagenomic Insights into Transferable Antibiotic Resistance in Oral Bacteria. (August 2016) - Sukumar, S.; Roberts, A.P.; Martin, F.E.; Adler, C.J.
Antibiotic resistance is considered one of the greatest threats to global public health. Resistance is often conferred by the presence of antibiotic resistance genes (ARGs), which are readily found in the oral microbiome. In-depth genetic analyses of the oral microbiome through metagenomic techniques reveal a broad distribution of ARGs (including novel ARGs) in individuals not recently exposed to antibiotics, including humans in isolated indigenous populations. This has resulted in a paradigm shift from focusing on the carriage of antibiotic resistance in pathogenic bacteria to a broader concept of an oral resistome, which includes all resistance genes in the microbiome. Metagenomics is beginning to demonstrate the role of the oral resistome and horizontal gene transfer within and between commensals in the absence of selective pressure, such as an antibiotic. At the chairside, metagenomic data reinforce our need to adhere to current antibiotic guidelines to minimize the spread of resistance, as such data reveal the extent of ARGs without exposure to antimicrobials and the ecologic changes created in the oral microbiome by even a single dose of antibiotics. The aim of this review is to discuss the role of metagenomics in the investigation of the oral resistome, including the transmission of antibiotic resistance in the oral microbiome. Future perspectives, including clinical implications of the findings from metagenomic investigations of oral ARGs, are also considered.